Agkistrodon acutus-purified protein C activator protects human umbilical vein endothelial cells against H2O2-induced apoptosis. (1st December 2016) - Li, Shu; Hong, Yun; Jin, Xin; Li, Xianwei; Sun, Entao; Zhang, Genbao; Lu, Linming; Nie, Liuwang
Abstract: Context: Recent studies show that the Agkistrodon acutus (Viperidae) (syn. Deinagkistrodon acutus ) protein C activator (PCA) treats acute myocardial infarction and ischaemia-reperfusion animal models effectively, while the underlying mechanism remains unknown. Objective: To study the effect of PCA on the injury of human umbilical vein endothelial cells (HUVECs) induced by H2 O2 and the underlying mechanism. Materials and methods: Primary cultured HUVECs were pretreated with PCA (20, 40 and 80 μg/mL) for 1 h, then HUVEC apoptosis was induced by 300 μmol/mL H2 O2 . Apoptosis was analyzed by AnnexinV-FITC/PI, and reactive oxygen species (ROS) level was tested by flow cytometry. Colorimetric methods were used to detect the levels of NO and IL-1. In addition, real-time PCR and western blot analyses were used to detect the expression of eNOS and phospho-p38/MAPK. Results: Morphological changes were induced by H2 O2 in HUVECs. The cell survival rate was increased by 43.9, 64.0 and 80.6% in each PCA pretreated group (20, 40 and 80 μg/mL) compared to the model group. In each PCA pretreated group, oxidative stress level was also decreased to 54.7, 42.7 and 25.1%. Moreover, the level of IL-1 was decreased to 83.3, 62.2 and 30.7%. The level of NO was increased by 155.9, 232.4 and 317.6%. Apoptosis rate was decreased to 59.0, 47.7 and 32.7%. Phospho-p38 expression was downregulated, but eNOS expression was upregulated. Discussion and conclusion: The results suggest that PCA can effectively protect the endothelial cells from injury induced by H2 O2, which may be associated with antioxidation, upregulation of eNOS and downregulation of p38-MAPK.